THE EFFECT OF GCG ON COMPANY PERFORMANCE WITH EXECUTIVE COMPENSATION AS A MODERATING VARIABLE - Apriyani, Duwi; Muharam, Harjum (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to analyze the effect of GCG on companies with executive compensation as a moderating variable. This study uses quantitative methods and the object of research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. This research uses. The results of this study indicate that institutional ownership has no significant effect on company performance. Managerial Ownership has a positive effect on Company Performance. The Independent Board of Commissioners has a positive effect on Company Performance. The Audit Committee has a positive effect on Company Performance. So the fourth hypothesis in this study is accepted. KI.EC has no significant effect on company performance. KM.EC does not have a significant effect on Company Performance. DKI.EC has a positive effect on Company Performance. So the fourth hypothesis in this study is accepted. KA.EC has no significant effect on Company Performance. So the fourth hypothesis in this study is rejected.